The relationship between employee satisfaction and employment tenure in hospitality organizations in Malaysia / Rahman Abdullah, Harnizam Zahari and Nik Adnan Nik Mat - Abdullah, Rahman; Zahari, Harnizam; Nik Mat, Nik Adnan (2013)
Many hospitality organizations faces issues in retaining employees since they are unable to identify which factor are the contributor to both satisfaction and employment tenure of the employee. This study would endeavor to identify which factor could actually make employees stay in their current working place while at the same time to see the linkage between employee satisfaction and employee loyalty which leads to employment tenure. In order to do that, a business model called Service Profit Chain was used and applied in selected hotels in Malaysia. A fraction of the model that identifies employee satisfaction and employee loyalty had been used in the questionnaire which was then tested to see the linkage of both variables. The findings indicate the existence of strong relationship between employee satisfaction and employee loyalty. The relationship is evident in terms of relationship with supervisor, training programs and benefits package which corresponds with all three aspect of loyalty in this study, employment tenure, planning future career with company and recommending employment. In other words, if these three variables are well entertained by the organizations, the creation of employee satisfaction which leads to employee loyalty and eventually builds long term employment tenure is very much possible in the hospitality industry which is plagued by high frequency of employment turnover.